Gut microbiota modulation in patients with non-alcoholic fatty liver disease: Effects of current treatments and future strategies - Marta Maestri; Francesco Santopaolo; Maurizio Pompili; Maurizio Pompili; Antonio Gasbarrini; Antonio Gasbarrini; Francesca Romana Ponziani; Francesca Romana Ponziani (Frontiers in Nutrition, 2023)
Non-alcoholic fatty liver disease (NAFLD) is frequently associated with metabolic disorders, being highly prevalent in obese and diabetic patients. Many concomitant factors that promote systemic and liver inflammation are involved in NAFLD pathogenesis, with a growing body of evidence highlighting the key role of the gut microbiota. Indeed, the gut-liver axis has a strong impact in the promotion of NAFLD and in the progression of the wide spectrum of its manifestations, claiming efforts to find effective strategies for gut microbiota modulation. Diet is among the most powerful tools; Western diet negatively affects intestinal permeability and the gut microbiota composition and function, selecting pathobionts, whereas Mediterranean diet fosters health-promoting bacteria, with a favorable impact on lipid and glucose metabolism and liver inflammation. Antibiotics and probiotics have been used to improve NAFLD features, with mixed results. More interestingly, medications used to treat NAFLD-associated comorbidities may also modulate the gut microbiota. Drugs for the treatment of type 2 diabetes mellitus (T2DM), such as metformin, glucagon-like peptide-1 (GLP-1) agonists, and sodium-glucose cotransporter (SGLT) inhibitors, are not only effective in the regulation of glucose homeostasis, but also in the reduction of liver fat content and inflammation, and they are associated with a shift in the gut microbiota composition towards a healthy phenotype. Even bariatric surgery significantly changes the gut microbiota, mostly due to the modification of the gastrointestinal anatomy, with a parallel improvement in histological features of NAFLD. Other options with promising effects in reprogramming the gut-liver axis, such as fecal microbial transplantation (FMT) and next-generation probiotics deserve further investigation for future inclusion in the therapeutic armamentarium of NAFLD.